2016
DOI: 10.1038/ncomms12456
|View full text |Cite
|
Sign up to set email alerts
|

The myosin X motor is optimized for movement on actin bundles

Abstract: Myosin X has features not found in other myosins. Its structure must underlie its unique ability to generate filopodia, which are essential for neuritogenesis, wound healing, cancer metastasis and some pathogenic infections. By determining high-resolution structures of key components of this motor, and characterizing the in vitro behaviour of the native dimer, we identify the features that explain the myosin X dimer behaviour. Single-molecule studies demonstrate that a native myosin X dimer moves on actin bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(149 citation statements)
references
References 71 publications
(140 reference statements)
8
140
0
1
Order By: Relevance
“…During the preparation of this paper, Ropers et al 32. reported that full-length myosin-X moves on single actin filaments with ~36 nm step size, and on synthetic fascin-actin bundles with 19 nm, 38 nm and 52 nm steps.…”
Section: Discussionmentioning
confidence: 98%
“…During the preparation of this paper, Ropers et al 32. reported that full-length myosin-X moves on single actin filaments with ~36 nm step size, and on synthetic fascin-actin bundles with 19 nm, 38 nm and 52 nm steps.…”
Section: Discussionmentioning
confidence: 98%
“…For example, TNFaip2/M-Sec utilizes the RalA GTPase and exocyst complex to initiate mNT formation (53,54), and are recruited along with filamin and myosin to the plasma membrane by the MHC class III protein, LST1 (44), to initiate mNT formation. Although it is yet unclear which cytoskeletal motors are responsible for mNT-mediated mRNA transfer, the velocity of the RNP particle shown in Movie S1 strongly resembles that of myosin motors (55,56). In particular, Myosin Va is involved in RNA trafficking (57) and is probably a good candidate to explore given that earlier work suggested a role for this motor in the distribution of Schwann cell-synthesized RNA to neuronal cell bodies and axons after lesioning (58).…”
Section: Is Mrna Transfer Solely Expression-dependent?mentioning
confidence: 95%
“…These distinctions may represent important regulatory factors that serve to guide specific myosins to the proper actin networks in vivo [21]. Indeed, in vitro assays have demonstrated that Myo10 prefers actin bundles as compared to single actin filaments [2224 • ]. Track selectivity of Myo10 is also likely mediated by its anti-parallel coiled-coil, which is required for its function in filopodial induction [25].…”
Section: Movement and Localization Of Myth4-ferm Myosins In Protrusionsmentioning
confidence: 99%
“…Track selectivity of Myo10 is also likely mediated by its anti-parallel coiled-coil, which is required for its function in filopodial induction [25]. This structural feature enables a wider range of step sizes [23,24 • ,26], which provides access to multiple actin binding sites within the bundle; this in turn might allow Myo10 to navigate around obstacles posed by other actin binding proteins found within the filopodium. Through its PH domains, Myo10 binds to and is regulated by its interaction with phosphatidylinositol-3,4,5-triphosphate [10,27], which may act as a method of localized activation since this lipid is enriched in the leading edge of migrating cells, the site of filopodial formation [2830].…”
Section: Movement and Localization Of Myth4-ferm Myosins In Protrusionsmentioning
confidence: 99%